Hubungan Kualitas Tidur Dengan Tingkat Insomnia Pada Lansia Binaan PSTW Nirwana Puri Kota Samarinda Kalimantan Timur - bahtiar, bahtiar; Ramadania, Riska; Nopriyanto, Dwi; Nur, Syukma (Alauddin Scientific Journal of Nursing, 2024)
Sleep quality refers to the ease of initiating and maintaining sleep, the duration of sleep, and any discomfort experienced during sleep or upon awakening. Insomnia, a common issue among the elderly, hinders their ability to sleep. The objective of this study was to establish the correlation between sleep quality and the degree of insomnia among the senior residents receiving assistance at the Nirwana Puri Social Tresna Werdha Home (PSTW) in Samarinda City, East Kalimantan. A cross-sectional research survey approach was employed to collect data from a sample of 52 older individuals. The Pittsburgh Sleep Quality Index tool was utilized to assess sleep quality, while the Insomnia Rating Scale was employed to gauge the severity of insomnia. The data analysis in this study employed the Chi-Square test. The findings indicated a significant correlation between sleep quality and the severity of insomnia in the elderly (p=0.002). The relationship between sleep quality and the level of insomnia in the elderly at PSTW Nirwana Puri Samarinda City is evident. Consequently, healthcare professionals must devise therapies to address sleep issues in older individuals in order to enhance their quality of life.